Hedonic housing valuation. An application with environmental variables (2014)
Through the utilization of spatial econometrics techniques, it was estimated the effect of some environmental variables on the price of urban housing in the city of Manizales, having as a source the council tax database with resulting use of the update done by IGAC in 2010. Finding that in average houses near to risky areas reduce their price up to 11%, the ones near a slope by 37% and those located in geotechnical treatment area up to 53%.